ANALISIS EFEK INTRA INDUSTRI PADA PENGUMUMAN PEMBAGIAN DIVIDEN PT TELKOM TAHUN 2006-2011 - , Lely Heryana ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study was to determine whether the market reacts to dividend announcements made by PT Telkom, and whether there are other companies in the telecommunications industry affected by intra-industry effects (both the contagion effects and competitive effects) due to the event. Data obtained from the dividend announcement event at the shareholders meeting, whether final dividend or interim dividend, from year 2006 to 2011. The sample in this study is the entire population, the telecommunications company whose shares are listed on the Indonesia Stock Exchange (IDX) up to December 2010. The method used in this study is the event study. In the test of the first hypothesis is obtained by comparing the maximum and minimum values, as well as the percentage change in stock price of PT Telkom in a period of one month prior to the event. The second hypothesis testing is done by testing the abnormal stock return of each other telecom companies at each event. The results showed that the dividend announcement PT Telkom did not have information content, and there are no intra-industry effects on other telecommunications companies to the event.